How to win at the ecology game 2 - Botkin, Daniel B. (Henry Stewart Talks, 2021)
Adaptation, Stromatolite, Biological Evolution, Mutation, Natural Selection, Migration, geographic isolation, and genetic drift, Thermodynamics, Ecosystem, Meaning of Life